2002
DOI: 10.1097/00004424-200209000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis for the Prevention of Contrast-Induced Nephropathy

Abstract: Data provide no hint that haemodialysis prevents contrast-induced nephropathy. Therefore, postprocedural dialysis should be restricted to patients participating in clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…134 However, several studies have failed to show that prophylactic hemodialysis soon after contrast-medium exposure is effective in preventing CIAKI in patients who are not already on renal replacement therapy. 135137 Hemodialysis has failed to prevent CIAKI even when dialysis was performed within 1 h of contrast-medium administration 138 or concurrently with coronary angiography, 139 and results from one study suggested that prophylactic hemodialysis might actually cause harm when performed after administration of contrast medium to patients with renal insufficiency. 140 However, the CIN Consensus Working Panel agreed that in patients with severe renal impairment (eGFR <20 ml/min) who require contrast-medium administration, hemodialysis should be undertaken if CIAKI develops.…”
Section: Ciaki Prevention In Diabetic Patientsmentioning
confidence: 99%
“…134 However, several studies have failed to show that prophylactic hemodialysis soon after contrast-medium exposure is effective in preventing CIAKI in patients who are not already on renal replacement therapy. 135137 Hemodialysis has failed to prevent CIAKI even when dialysis was performed within 1 h of contrast-medium administration 138 or concurrently with coronary angiography, 139 and results from one study suggested that prophylactic hemodialysis might actually cause harm when performed after administration of contrast medium to patients with renal insufficiency. 140 However, the CIN Consensus Working Panel agreed that in patients with severe renal impairment (eGFR <20 ml/min) who require contrast-medium administration, hemodialysis should be undertaken if CIAKI develops.…”
Section: Ciaki Prevention In Diabetic Patientsmentioning
confidence: 99%
“…We identified 14 studies that compared renal outcomes between patients undergoing and those not undergoing extracorporeal blood purification for RCIN. 13,[17][18][19][20][21][22][23][24][25][26][27][28][29] Of these, 9 dealt with hemodialysis for the prevention of RCIN: 5 were randomized trials, 17,18,[20][21][22] and the sixth used a case-control design. 19 The seventh study described results in the context of previous studies without their own comparison group and therefore was not eligible.…”
Section: Identification Of Eligible Trialsmentioning
confidence: 99%
“…19 The seventh study described results in the context of previous studies without their own comparison group and therefore was not eligible. 23 The eighth study was a similar report in German of the same patients reported in an English language journal and also was excluded. 24 The ninth article was a letter to the editor describing the outcome of some of the patients reported in a previous study.…”
Section: Identification Of Eligible Trialsmentioning
confidence: 99%
“…Although this difference was not found to be statistically significant, it does pose important questions regarding the use of prophylactic haemodialysis for the prevention of CIN. A recent study by Huber et al [41] assessed the outcomes of 31 patients with a baseline mean serum creatinine of 4.01 ± 1.83 mg/dl who underwent haemodialysis after a contrast procedure to prevent CIN. Despite a significant reduction in serum creatinine after dialysis (2.25 ± 1.46 mg/dl; p < 0.0001), 19 of 31 patients (61%) had an increase of ≥ 0.5 mg/dl in serum creatinine levels within 7 days of the procedure.…”
Section: Dialysismentioning
confidence: 99%
“…Therefore, based on the results from these studies, there is no net benefit from prophylactic haemodialysis and it cannot be recommended to renal insufficiency patients undergoing contrast-mediated procedures. Those who perform haemodialysis for prophylaxis are reminded that although elevated serum creatinine levels may be reduced using dialysis, many patients experience a return to predialysis levels within several days [40,41]. In dialysis patients, serum creatinine levels may not accurately reflect renal function and a more thorough evaluation of both the pre-and postdialytic glomerular filtration rate is warranted [42].…”
Section: Dialysismentioning
confidence: 99%